A Noble Education: Sustainability education in the 21st Century. - John, Michele (2025)
This Handbook endeavours to provide a comprehensive introduction to sustainability education as a ‘noble education’, including important sustainability contexts, the language and core concepts in sustainability thinking, key competencies for sustainability education, pedagogies and strategies for teaching sustainability, the role of ethics and stewardship responsibilities in sustainability management, and the importance of university sustainability leadership in the sustainability transition. A noble ‘sustainability-focused’ education will require educators to encourage transformative learning that highlights the life cycle impacts of our production and consumption activities on the environment, together with the development of curricula that can support the formation of a sustainability mindset that empowers sustainability action.